Covernote Notaris dalam Perjanjian Kredit Perspektif Hukum Jaminan (Studi Kasus PN Kab. Kediri Nomor 107/Pdt.G/2020/PN Gpr) - Gede Indra Fredy Baskara; I Made Pria Dharsana; Ni Gusti Ketut Sri Astiti (Fakultas Hukum Universitas Warmadewa, 2024)
Credit is the provision of money and types of loans that must be paid back. Credit has a high risk for banks, so notaries as public officials make cover notes in credit agreements. The formulation of the problem discussed is How is the Authority and Responsibility of Notaries in Credit Agreements and How is Legal Protection for Creditors in Credit Agreements Related to the Use of Notary Covernote? The research method used is normative juridical. The results showed that the obligations and responsibilities of notaries in credit agreements are to bridge the interests of creditors and borrowers in making deeds to credit agreements. Lending and borrowing agreements are regulated in the Civil Code Article 1754 to Article 1769. Legal protection for bank creditors in credit agreements using notary covernote in the event of default before the issuance of mortgage rights gives the bank's position only as a concurrent creditor and legal protection for banks is based on Articles 1131 and 1132 of the Civil Code.